Family Aggregation in Individuals with Essential Arterial Hypertension and Risk Factors - Julio Armando Sánchez Delgado; Nailé Edita Sánchez Lara (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Background: arterial hypertension is the constant elevation of blood pressure figures with a polygenic and multifactorial origin. Hypertension is a disease of high incidence and prevalence worldwide. Objective: to demonstrate the familial aggregation for essential arterial hypertension and risk factors in affected individuals. Method: an observational, analytical, longitudinal and retrospective case / control investigation was carried out from the reference consultation for chronic non-communicable diseases in Banes, Holguín province during the period from October 2019 to March 2020. The universe covered all individuals diagnosed and their families. By simple random sampling, the sample of 91 cases was obtained. The control group was formed at a ratio of 3:1 which included 273 individuals. Bioethical requirements were met. Inclusion / exclusion criteria were applied. The following statistics were used: Chi square, Odd Ratio (OR), including p and confidence interval. The variables were operationalized: age, sex, degree of consanguinity, and risk factors. The genealogical tree was obtained. Results: the age groups 56-65 years and 66 years and over, were the most affected. The male sex predominated (53.9 %). First and second-degree relatives of consanguinity showed the highest incidence of the disease. An association was found between the disease and its family history (X2 = 321.4) with an increased risk for relatives of the cases compared to the controls (OR = 10.93). The predominant risk factors were: smoking (OR = 2.18) and family history of disease (OR = 0.74). The association of risk factors with the disease was demonstrated (X2 = 176.9). Conclusions: essential arterial hypertension is a multifactorial, complex and polygenic disease with demonstrated familial aggregation.